2008
DOI: 10.1097/bsd.0b013e31816d655e
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Occipital Condyle Screw Placement for Occipitocervical Fixation

Abstract: Condyle screws can be placed without injury to neurovascular structures. OC junction fixation using polyaxial occipital condyle screws is feasible and can be considered a salvage technique or an alternative where other fixation techniques are not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 38 publications
1
57
0
Order By: Relevance
“…4 This procedure was based on prior publications validating the technique in cadavers. 31 Our technique, used in the pediatric cases described here, was adapted from previous work published by Frankel et al 6 analyzing the occipital condyles in 40 patients using CT scans, and confirming screw length, trajectory, and feasibility in 4 adult cadavers. From this analysis the authors concluded that, on average, a 3.5-mm-diameter screw, 20-to 30-mm in length, can be safely placed at an angle of 20°-33° from the sagittal plane (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 This procedure was based on prior publications validating the technique in cadavers. 31 Our technique, used in the pediatric cases described here, was adapted from previous work published by Frankel et al 6 analyzing the occipital condyles in 40 patients using CT scans, and confirming screw length, trajectory, and feasibility in 4 adult cadavers. From this analysis the authors concluded that, on average, a 3.5-mm-diameter screw, 20-to 30-mm in length, can be safely placed at an angle of 20°-33° from the sagittal plane (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Adult cadaveric studies have demonstrated the occipital condyles (C-0) to be a feasible fixation point. 4,6,13,14,21,[30][31][32] Subsequently, successful demonstration of this technique has been reported in adults 6,30 and in 1 pediatric patient. 4 In this paper, we present a series of 4 pediatric patients using our described technique.…”
mentioning
confidence: 99%
“…7,8,13,19,20) The theoretical advantage of condylar screw fixation is the lower profile and no dependence on the thickness of the occipital bone. Furthermore, there is no risk of creating potential epidural hematoma.…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest concerns is the anatomical feasibility of placing the screw at the occipital condyle. 13,20) Screw malposition may cause major complications involving the medulla, hypoglossal nerve, venous plexus, or vertebral artery. Another concern is the biomechanical strength of these screw constructs.…”
Section: Introductionmentioning
confidence: 99%
“…In our technique, the condylar entry point corresponds to the midcondylar area, 4 to 5 mm lateral to the foramen magnum on the axial plane and 1 to 2 mm rostral to the atlantooccipital joint. 4 In the technique of Frankel et al, caudal-cranial angulation is determined by placing the hand drill in the pilot hole with its shaft tangential to and abutting the skull base. Depending on condylar, skull base, and hypoglossal canal anatomy, the overall trajectory of occipital condyle screws is usually 10° cranial or caudal to the horizontal plane.…”
Section: Occipital Condyle To Cervical Spine Screw and Rod Fixationmentioning
confidence: 99%